2017
DOI: 10.11607/jomi.5431
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Digital vs Conventional Implant Impression Approach: A Three-Dimensional Comparative In Vitro Analysis

Abstract: Purpose: To assess the three-dimensional (3D) accuracy and clinical acceptability of implant definitive casts fabricated using a digital impression approach and to compare the results with those of a conventional impression method in a partially edentulous condition. Materials and Methods: A mandibular reference model was fabricated with implants in the first premolar and molar positions to simulate a patient with bilateral posterior edentulism. Ten implant-level impressions per method were made using either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 32 publications
6
53
0
4
Order By: Relevance
“…Conventional impression techniques require several clinical and laboratory steps, which could introduce flaws . The developments in digital technology give clinicians the option to digitally scan the structures . While the accuracy of various implant impression techniques has been the subject of several studies and many techniques have been reported both in conventional and digital implant scans, there are conflicting reports regarding the superiority of the impression technique's accuracy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional impression techniques require several clinical and laboratory steps, which could introduce flaws . The developments in digital technology give clinicians the option to digitally scan the structures . While the accuracy of various implant impression techniques has been the subject of several studies and many techniques have been reported both in conventional and digital implant scans, there are conflicting reports regarding the superiority of the impression technique's accuracy .…”
Section: Introductionmentioning
confidence: 99%
“…The developments in digital technology give clinicians the option to digitally scan the structures . While the accuracy of various implant impression techniques has been the subject of several studies and many techniques have been reported both in conventional and digital implant scans, there are conflicting reports regarding the superiority of the impression technique's accuracy . Some studies reported that the accuracy of digital implant scans are comparable with conventional impressions …”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found that digital impressions resulted in better marginal and internal fit than conventional for tooth-supported single crowns and FDPs (Chochlidakis et al, 2016). Regarding implant-supported prostheses, there are less available data currently, but there is a constant increase of published data on the accuracy of digital impressions with IOS systems, and the results seem promising for both partially and fully edentulous arches (Amin et al, 2017;Basaki, Alkumru, Souza, & Finer, 2017;Chew et al, 2017;Chia et al, 2017;Lee, Betensky, Gianneschi, & Gallucci, 2015;Marghalani et al, 2018;Papaspyridakos et al, 2016;Papaspyridakos, Rajput, Kudara, & Weber, 2017;Vandeweghe, Vervack, Dierens, & Bruyn, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, in a recent clinical study with 36 partial edentulous patients, digital impression exhibited least accuracy with linear errors ranging from 160 to 270 μm, and the authors conclude it is not suitable to fabricate a well‐fitting restoration with digital impressions . An in vitro study also supported this conclusion . The inconsistency of these results might be caused by various factors, such as different number and distribution of implants, types of intraoral scanning system, choice of digitalization methods, reference data, and evaluation methods.…”
Section: Discussionmentioning
confidence: 99%
“…36 An in vitro study also supported this conclusion. 37 The inconsistency of these results might be caused by various factors, such as different number and distribution of implants, types of intraoral scanning system, choice of digitalization methods, reference data, and evaluation methods. Until now, no consensus can be made regarding digital impression in fabricating multiple-implant-supported restoration.…”
Section: Study Participants 31mentioning
confidence: 99%